Uso da ultrassonografia do diafragma na avaliação da hiperinsuflação dinâmica no portador da doença pulmonar obstrutiva crônica - Andrade, Juliana Dantas (2016)
Introduction: Expiratory air flow limitation, as seen in individuals with chronic obstructive pulmonary disease (COPD), causes pulmonary hyperinflation and dyspnea. Six-minute walking test (6MWT) can be used to stimulate dynamic hyperinflation in COPD patients. Diaphragm mobility evaluation through M mode ultrasonography can be used to evaluate diaphragm dysfunction. The higher the diaphragmatic mobility, the bigger is the variation of muscle shortening resulting from its contraction. Objective: Measure, analyze and relate diaphragmatic mobility and ventilation parameters before and after 6MWT; to classify severity of COPD and to determine physical performance of patients. Materials and methods: Study design was transversal, analytical. The sample was divided in two groups: COPD and control (respiratory healthy individuals), recruited from Hospital Universitário de Sergipe and gyms in the city, evaluated between February 2015 and March 2016. Both groups were submitted to diaphragmatic mobility ultrasonographic evaluation and spirometry without bronchodilator agents before and after 6MWT, anthropometric measuring and answered COPD Assessment Test (CAT) and modified Medical Research Council (mMRC) dyspnea scale and had data about their disease collected. Results: After inclusion and exclusion criteria application, 70 patients remained in COPD group and 65 in Control group. There was significative reduction on diaphragmatic mobility between COPD and Control groups before (1,11±0,35cm; 1,32±0,38cm, respectively) and after (1,00±0,34cm; 1,37±0,35cm, respectively) 6MWT. Walked distance was also different between groups (395,93±70,54m and 450,63±55,08m, respectively, p<0,001). COPD group showed statistic difference before and after 6MWT in gender (p<0,001), smoking (p<0,001), biomass burning exposure (p<0,001), exacerbations (p<0,001), hospitalizations (p<0,001) and GOLD D severity (p=0,016). Conclusion: Significant difference in reduced diaphragmatic mobility in COPD and increased in healthy individuals and lower FVC in COPD without alterations in controls after exercise are suggestive of dynamic hyperinflation development. COPD patients distributed by GOLD severity classification were more frequently from Groups B and D. Mean walking distance was close to values considered of increased risk to mortality and hospitalization and are an alarm about the need to implement preventive measures (pharmacologic and non-pharmacologic) to improve this outcome.